(untitled) (Pedagogical Horizons, 2017)
This study evaluates an advanced training course dealing with gender topics. Using semi-structured interviews based on the Kirkpatrick model (Kirkpatrick &Kirkpatrick, 2006), it focuses on the motivation for participation and the effectiveness of the training from the perspective of participants across four levels. The evaluation reveals satisfaction on level one and a change in knowledge (level two) and behaviour (level three). Furthermore the interviewees perceive an increased gender awareness on the part of their pupils – which corresponds to a change on the fourth level. This means there is clear evidence that this training course is to be regarded as highly effective. The positive evaluation, however, contrasts the motivation for participation, as it is only described as extrinsic by most of the interviewees. These results illustrate a general dilemma of effective training courses: as they are per definition time- and resources consuming people are all too frequently discouraged from participating. Therefore the characteristic features contributing to the effectiveness of trainings are at the same time educational barriers.